Reflections on Dual Regulation of Securities: A Case for Reallocation of Regulatory Responsibilities - Manning Gilbert Warren III (Washington University Law Quarterly, 2000)
I address the scope of state regulatory power that remains given the National Securities Markets Improvement Act of 1996's dictates and prerogatives. I then suggest for consideration significant alterations to the regulatory role traditionally performed by the states.
Keywords: Exclusive & concurrent legislative powers; Blue sky laws; Preemption (Legislative power); Securities law; National Securities Markets Improvement Act of 1996